Indolylbenzothiadiazoles as highly tunable fluorophores for imaging lipid droplet accumulation in astrocytes and glioblastoma cells. Issue 39 (6th July 2021) - Colas, Kilian; Holmberg, Karl O.; Chiang, Linus; Doloczki, Susanne; Swartling, Fredrik J.; Dyrager, Christine
Abstract : We present an extensive photophysical study of a series of fluorescent indolylbenzothiadiazole derivatives and their ability to specifically image lipid droplets in astrocytes and glioblastoma cells. Abstract : We present an extensive photophysical study of a series of fluorescent indolylbenzothiadiazole derivatives and their ability to specifically image lipid droplets in astrocytes and glioblastoma cells. All compounds in the series displayed positive solvatochromism together with large Stokes shifts, and π-extended derivatives exhibited elevated brightness. It was shown that the fluorescence properties were highly tunable by varying the electronic character or size of the N -substituent on the indole motif. Three compounds proved capable as probes for detecting small quantities of lipid deposits in healthy and cancerous brain cells. In addition, all twelve compounds in the series were predicted to cross the blood–brain barrier, which raises the prospect for future in vivo studies for exploring the role of lipid droplets in the central nervous system.